2013
DOI: 10.1016/j.cell.2013.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Recruitment to Nuclear Pores Activates Apical Nuclear Migration and Mitotic Entry in Brain Progenitor Cells

Abstract: Summary Radial glial progenitors (RGPs) are elongated epithelial cells which give rise to neurons, glia, and adult stem cells during brain development. RGP nuclei migrate basally during G1, apically using cytoplasmic dynein during G2, and undergo mitosis at the ventricular surface. By live imaging of in utero electroporated rat brain, we find that two distinct G2-specific mechanisms for dynein nuclear pore recruitment are essential for apical nuclear migration. The “RanBP2-BicD2” and “Nup133-CENP-F” pathways a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
248
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(269 citation statements)
references
References 47 publications
20
248
1
Order By: Relevance
“…In these cells, nuclei undergo cell cycle dependent movement, and move towards the ventricular surface during G2, and then go through mitosis when the nuclei reach the surface. Interestingly, this movement is centrosome-independent (Tsai et al, 2010), and does not appear to involve the LINC complex (Hu et al, 2013). 3D structured illumination microscopy clearly showed that BicD2 (the Nup358-binding dynein/dynactin adaptor), dynein and dynactin localize to the cytoplasmic face of the NPC in G2, whereas CENP-F (required for Nup133-dependent dynein/dynactin recruitment) only binds later, in prophase.…”
Section: Microtubule Attachment To the Npc-associated Y-complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cells, nuclei undergo cell cycle dependent movement, and move towards the ventricular surface during G2, and then go through mitosis when the nuclei reach the surface. Interestingly, this movement is centrosome-independent (Tsai et al, 2010), and does not appear to involve the LINC complex (Hu et al, 2013). 3D structured illumination microscopy clearly showed that BicD2 (the Nup358-binding dynein/dynactin adaptor), dynein and dynactin localize to the cytoplasmic face of the NPC in G2, whereas CENP-F (required for Nup133-dependent dynein/dynactin recruitment) only binds later, in prophase.…”
Section: Microtubule Attachment To the Npc-associated Y-complexmentioning
confidence: 99%
“…Another interesting example of nuclear movement is in the radial glial progenitor cells involved in neuronal and glial development (Hu et al, 2013). In these cells, nuclei undergo cell cycle dependent movement, and move towards the ventricular surface during G2, and then go through mitosis when the nuclei reach the surface.…”
Section: Microtubule Attachment To the Npc-associated Y-complexmentioning
confidence: 99%
“…RGP nuclei migrate basally during G1, then apically during G2 via dynein, and eventually divide at the ventricular surface. Hu et al (2013) discovered that apical nuclear migration requires dynein recruitment at NPCs by two cooperating G2-specific mechanisms: the "RanBP2-BicD2" pathway acts first, and "Nup133-CENP-F" operates sequentially. This work identifies spatially regulated mechanisms, implying that only restricted regions of neurogenic tissues are permissive for mitosis: in this context, RANBP2 is essential for dynein control of apical nuclear migration, nuclear membrane remodelling and centrosome dynamics prior to mitosis.…”
Section: Ranbp2 In Interphase Nucleocytoplasmic Transportmentioning
confidence: 99%
“…Mitosis occurs only when the cell body is at the ventricular surface. 2 Once in G1, the nucleus migrates away from the ventricular surface through the narrow basal process of the cell, progresses through Sphase, and then returns to the ventricular surface during G2 for the next mitotic division (Fig. 1).…”
mentioning
confidence: 99%
“…2,4 Early G2 nuclear envelope recruitment is activated by Cdk1 phosphorylation of the nucleoporin RanBP2, which, in turn, recruits BicD2, dynein, dynactin, and Lis1. Late G2 nuclear envelope recruitment involves another nucleoporin, Nup133, which recruits CENP-F once it has left the late G2 nucleus through an incompletely understood Cdk1-mediated mechanism.…”
mentioning
confidence: 99%